Financial Accessibility of Small and Medium Enterpraise (SMEs) in Surakarta City - Hakim, Muhammad Luqman; Ningsih, Mardhiyatur Rosita (JIFA (Journal of Islamic Finance and Accounting), 2020)
Small and Medium Enterprise (SMEs) is priority economics sector until 65 percent in Indonesia. It had been priorities focus of government policy to financial access in banking helped SMEs. The research is aim to analyze the influence of SMEs Characteristic, Financial Literacy, and Lending Term toward Financial Accessi- bility SMEs in Surakarta city. The research had sample from SMEs registered in SMEs government in Surakarta city is 100 sample. Sample of the research with proportionate stratified random sam- pling technique. Methodology in this research is regression. The Re- sult of this research state that the SMEs Characteristics, Financial Literacy, and Lending term positif toward Financial Accessibility Keywords: Financial Accessibility, Financial Literacy, Lending Term, SMEs Characteristics JEL Classification: G32, L22,L26